The System of Indicators for Assessing the Effectiveness of the Regions in the Field of Tourist Services in Russia: Key Problems and Solutions - ROMANYUK, Anton V.; GAREEV, Roman R. (Journal of Environmental Management and Tourism; Vol 11 No 6 (2020): JEMT Volume XI, Issue 6(46) Fall 2020, 2020)
The aim of the present research is to identify ways to improve the assessment of the effectiveness of the Russian Federation's subjects in the field of tourism. The article presents the main factors by which it is proposed to assess the attractiveness of a tourist destination. The analysis showed that it is necessary to unify the set of indicators that should be used in assessing the effectiveness of the activities of the subjects of the Russian Federation in the field of tourism. Author presents the composition of indicators characterizing the attractiveness of a tourist destination. Recommendations for maintaining an information base for assessing the effectiveness of the activities of the entities of the Russian Federation in the field of tourism allowed the authors to offer an assessment of tourism development in the region as a criterion of efficiency of activity of the subject of the Russian Federation. The paper highlighted the main criteria for assessing the effectiveness of the subjects of the Russian Federation in the field of tourism.